International corporate cash holdings and firm-level exposure to COVID-19: Do cultural dimensions matter? - Khanh Hoang; Cuong Nguyen; Dung Viet Tran; Anh Phan (Journal of Risk and Financial Management, 2022)
This study investigates the impact of COVID-19 exposure on corporate cash holdings using firm data across sixteen developing and developed economies. The results show that firms reserve more cash when their exposure to COVID-19 increases. We also find a cash burn effect during the COVID-19 pandemic, meaning that the cash holdings are drained when firm exposure to the pandemic exceeds a tipping point. The effect is more pronounced in larger firms and firms with less cash reserve. Further analyses reveal that the cash burn effect tends to be stronger in countries with a high level of individualism and weaker in countries with high levels of risk aversion, masculinity, and long-term orientation. The findings provide fresh insights into the connections among corporate cash holdings, national cultures, and firm-level exposure to COVID-19.
Keywords: 650; cash burn effect; cash holdings; COVID-19; national culture